Biology and the Development of Style of Thinking of Natural Sciences - Meščeriakova, Natalija (Problemos, 1977)
The paper gives definition of the style of thinking of natural sciences, as a general trend of scientific research and a unique norm of thinking characteristic of each epoch. Tue idea that a contemporary style of thinking in its most general and essential form might be defined as the realization of dialectics is motivated theoretically. Comparatively concrete characteristics of this definition are presented.